Portraits of the Ptolemies : Greek kings as Egyptian pharaohs - Stanwick, Paul Edmund (University of Texas Press, 2002)
"In this book, Paul Edmund Stanwick undertakes the first complete study of Egyptian-style portraits of the Ptolemies. Examining one hundred and fifty sculptures from the vantage points of literary evidence, archaeology, history, religion, and stylistic development, he fully explores how they meld Egyptian and Greek cultural traditions and evoke surrounding social developments and political events. To do this, he develops a "visual vocabulary" for reading royal portraiture and discusses how the portraits helped legitimate the Ptolemies and advance their ideology. Stanwick also sheds new light on the chronology of the sculptures, giving dates to many previously undated ones and showing that others belong outside the Ptolemaic period."--Jacket